FORMATION OF REQUIREMENTS FOR THE INFORMATION SYSTEM OF SUPPORTING DECISION-MAKING IN THE FIELD OF MANAGEMENT OF URBAN PASSENGER TRANSPORT - Anatoliy Sorokin; Anna Orlova (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the elements of high-level requirements for the creation of an integrated information system for decision-making in the management of urban passenger transport. The user groups, the necessary functionality for each of them are considered. The logical structure of the system modules is given. The groups of effects from the implementation of the decision-making information system in the field of urban passenger transport management are described in terms of: social, managerial, commercial effects and effect in the ield of trafic safety.